2010
DOI: 10.1101/gad.1989510
|View full text |Cite
|
Sign up to set email alerts
|

Roles for the Yb body components Armitage and Yb in primary piRNA biogenesis in Drosophila

Abstract: PIWI-interacting RNAs (piRNAs) protect genome integrity from transposons. In Drosophila ovarian somas, primary piRNAs are produced and loaded onto Piwi. Here, we describe roles for the cytoplasmic Yb body components Armitage and Yb in somatic primary piRNA biogenesis. Armitage binds to Piwi and is required for localizing Piwi into Yb bodies. Without Armitage or Yb, Piwi is freed from the piRNAs and does not enter the nucleus. Thus, piRNA loading is required for Piwi nuclear entry. We propose that a functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
421
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 283 publications
(456 citation statements)
references
References 29 publications
29
421
0
6
Order By: Relevance
“…MOV10L1 does not interact with Tdrkh (Saxe et al 2013), which is required for 3 ′ end maturation. Experiments in Drosophila are consistent with our model; RNAs isolated from Armitage by standard immunoprecipitation conditions show characteristics similar to those of piRNA precursor fragments (Saito et al 2010). A significant number of Armitage-bound RNA fragments mapped within the flamenco locus, which gives rise to long piRNA precursor transcripts (Malone et al 2009), overlapping with piRNA sequences (Saito et al 2010).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…MOV10L1 does not interact with Tdrkh (Saxe et al 2013), which is required for 3 ′ end maturation. Experiments in Drosophila are consistent with our model; RNAs isolated from Armitage by standard immunoprecipitation conditions show characteristics similar to those of piRNA precursor fragments (Saito et al 2010). A significant number of Armitage-bound RNA fragments mapped within the flamenco locus, which gives rise to long piRNA precursor transcripts (Malone et al 2009), overlapping with piRNA sequences (Saito et al 2010).…”
Section: Discussionsupporting
confidence: 64%
“…There is substantial evidence from genetic and cell culture experiments that Zuc is essential for primary piRNA biogenesis (Pane et al 2007;Malone et al 2009;Haase et al 2010;Saito et al 2010;Watanabe et al 2011), and it was recently shown both structurally and biochemically that Zuc is an endonuclease that cleaves ssRNA and leaves a 5 ′ phosphate end (Ipsaro et al 2012;Nishimasu et al 2012;Voigt et al 2012). Therefore, Zuc fits the description for the endonuclease that generates the 5 ′ ends of piRNA intermediates, but direct proof of this is lacking.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the signals detected in the latter experiments probably reflect functions of somatic Piwi. Using an ovarian somatic cell line (OSC), Saito et al have shown that Piwi is required to maintain normal piRNA levels in these cells (17). Although the mechanism remains unclear, their results in soma taken together with our observations in germ line highlight a distinction in Piwi function between the two tissues.…”
Section: Discussionsupporting
confidence: 50%
“…In the germ line, piRNA biogenesis involves both primary processing and a secondary amplification pathway (ping-pong amplification) (8,9,16), whereas piRNAs in the soma are generated solely from primary transcripts (primary pathway) (14,15,17).…”
mentioning
confidence: 99%